Analysis of Government Expenditure on Private Sector Investment in Nepal: A Time Series Approach (Saptagandaki Journal, 2024)
This study examines the role of government expenditure on private sector investment in Nepal, utilizing a time-series approach. The research employs a quantitative methodology, analyzing 49 years of time-series data (1974/75-2022/23). The study uses the Autoregressive Distributed Lag (ARDL) model to explore both the long-run and short-run relationships between government expenditure and private investment. The dependent variable is private sector investment, while the independent variables include real GDP, government expenditure, foreign exchange rates, and the consumer price index (CPI). Unit root tests, the ARDL bounds test, and Granger causality tests were applied to analyze the data. The results indicate a significant positive long-run relationship between real GDP and private sector investment, while government expenditure shows mixed effects. Infrastructure-related government spending positively influences private investment, whereas non-infrastructure expenditure has a crowding-out effect. Inflation, represented by the CPI, has a negative impact on private sector investment, creating uncertainty and raising costs. The foreign exchange rate demonstrates a marginally significant positive effect on private investment. The findings align with previous research in developing countries where researchers observed the crowding-in effect of government spending on private investment. The role of inflation and foreign exchange stability was also highlighted as crucial for fostering a favorable investment environment.